Age-related patterns of early childhood development practices amongst rural families in Burkina Faso: findings from a nationwide survey of mothers of children aged 0-3 years. Issue 1 (31st December 2020) - Hollowell, Jennifer; Belem, Mireille; Swigart, Tessa; Murray, Joanna; Hill, Zelee
ABSTRACT: Background: Around two thirds of children in Sub-Saharan Africa are at risk of not meeting their developmental potential. Scalable interventions, based on an understanding of local contexts, that promote nurturing care in children's early years are needed. Objectives: To investigate age-related patterns of Early Childhood Development (ECD) practices amongst caretakers of children aged 0–3 years in rural households in Burkina Faso, in order to inform the design of a mass media campaign to be evaluated through a randomized controlled trial. Methods: A household survey using a structured questionnaire was used to collect data from 960 rural mothers of children aged 0–3 years in a regionally stratified random sample of 130 villages. Results: The mother was the main caretaker and engaged most in ECD-related activities at all ages (0–3 years). The father, grandmother and older children also engaged in ECD-related activities with older children (aged 1–3 years). Singing and playing occurred moderately frequently. Singing in the last three days: 36% at age 0–5 months increasing to 84% at age 3 years; playing in the last three days: 26% at age 0–5 months, increasing to 65% at age 3 years. Activities such as reading, counting, drawing, 'showing and naming' and 'chatting' were limited, particularly in the child's first year. Reasons for not engaging in these activities include lack of literacy, lack of books and toys or playthings and a belief that the child was too young. Conclusion: Opportunities for learning, especially through verbal interactions, appeared to be limited during the developmentally crucial first three years, most notably in the first year of life. The challenge for ECD intervention development in Burkina Faso will be finding ways to promote more responsive interactions at an early age and finding ways of mobilizing other family members to become more engaged in stimulating activities in the child's early years.